(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the problem of logical modality. The infinitive constructions as means of the expression of logical modality are defined. The attempt of analyses of ways of the expression of logical modality in the modern German language has been made.